Evaluation of Adaptation, Biomass Production, and Nutritive Value of Napier Grass Across Different Agro-Ecologies in the Somali Regional State, Ethiopia (American Journal of Aquaculture and Animal Science, 2025)
A study was conducted to evaluate the agronomic performance and nutritional quality of three Napier grass (Pennisetum purpureum) varieties, 16819, 16984, & 16791, under irrigated conditions at Fafan, Dolo Ado, and Godey agricultural research centers in the Somali Regional State, Ethiopia. The experiment followed a randomized complete block design (RCBD) with three replications, considering variety and location as factors. Data on growth, yield, and nutritive value were analyzed using ANOVA through the General Linear Model (GLM) procedure in SAS (2009). Results showed highly significant (P